PENGARUH CAPITAL INTENSITY, FINANCIAL DISTRESS DAN KONEKSI POLITIK TERHADAP TAX AVOIDANCE - Irmawati; Abidin, Jaenal (Jurnal Nusa Akuntansi, 2025)
This study aims to analyze the influence of capital intensity, financial distress and political connections on tax avoidance. This study was conducted by analyzing financial reports and annual reports of companies operating in the mining sector listed on the Indonesian Stock Exchange (BEI) for a 6 year period (2018-2023). The sample used in this study was 13 companies taken based on purposive sampling technique. The data used in this study is secondary data in the form of financial reports and annual reports from each company that has been used as a study sample. The independent variables in this study are capital intensity, financial distress and political connections, while the dependent variable is tax avoidance. This study uses the panel data regression method. Analysis of study results using the Eviews 12 Student Lite Version tool. The results of this study show that partially capital intensity has a negative effect on tax avoidance, financial distress have no significant effect on tax avoidance and political connections have no significant effect on tax avoidance. Simultaneously capital intensity, financial distress and political connections influence tax avoidance.